Staging innovation projects: (when) does it pay off? - Petra Andries; Paul Hünermund (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Building on real options literature, this study shows that the use of a staged approach for the management of innovation projects affects the innovation output of firms differently depending on firm characteristics and ambitions. In particular, while staged project management increases the effect of inno- vation expenditures on new product sales for firms envisaging incremental or continuous innovations, this moderating effect is absent for firms aspiring radical innovations. In addition, while staged project management has a pos- itive moderating effect in firms with resource slack, this is not the case when firms are resource-constrained. We further investigate the underlying mecha- nisms to this latter finding by demonstrating that in resource-abundant firms staged project organization is associated with delaying projects until more information becomes available. Thereby these firms reap the waiting value inherent to real options reasoning. By contrast, resource-constrained firms using staged project management are shown to abandon a larger share of their innovation projects and to concentrate resources on fewer projects. It appears, however, that, due to budgetary pressure, they make the decision to abandon at a too early stage where uncertainty is insufficiently resolved. This can explain why there is no effect of staged project management on the sales of resource-constrained firms from new products. The paper contributes to theory development on when and why the staging of innovation projects affects the innovation output of firms and to the literature on real options reasoning in general.
urn:nbn:de:bsz:180-madoc-373284
Keywords: O32; 330; staging of innovation projects; real options theory; new product development process; ressource allocation; innovation portfolios